(untitled) - Adams, Henry (Englewood Cliffs, New Jersey, 1963)
The book covers the chief evemts of Madison's administrations, concentrating on the War of 1812 and its consequences. Its deals with the " imbecility " of the 11th Congress, The War itself, the Hartford Convention, and the triump of union over disunion within his central theme: the rise, decline, and renewal of democratic nationalism.